Additive Combinatorics - Tao, Terence; Vu, Van H (Cambridge : Cambridge University Press, 2006)
Additive combinatorics is the theory of counting additive structures in sets. This theory has seen exciting developments and dramatic changes in direction in recent years thanks to its connections with areas such as number theory, ergodic theory and graph
Includes Bibliography 488-504p.; Index 505-512p.
Keywords: Additive combinatorics; Additive geometry; Probabilistics method; Mathematics